Christian zionism in the US: Its roots, founding principles and its influence in American politics [ABD’de Hıristiyan Siyonizmi: Kökeni, İnanç Esasları ve Günümüz Amerikan Siyasetine Etkisi] - ALBAYRAK, HAFİZE ŞULE (Istanbul Universitesi, 2019)
This article looks at Christian Zionism in the US from a sociological perspective. For this aim, I will examine the questions of “who are the Christian Zionists?”, “what constitutes the roots and fundamental doctrines of Christian Zionism?” and “how do Christian Zionists view world politics?” In this descriptive work, which aims to elaborate on an under-investigated research topic in Turkish academia, first I will provide a background into its history, dating back to 19th century Britain. Secondly, I will discuss the fundamental theological principles of Christian Zionism and the role played by Jews and Israel in this belief system. Lastly, the increasing influence of Christian Zionists over American politics will be discussed. ©Yazarlar.
Keywords: Christian Zionism; Evangelical; Fundamentalism; Ottoman Empire; United States of America